Analiza juridico-penală a legislației unor state cu o democrație consacrată privind incriminarea infracțiunilor electorale și coruperii alegătorilor [Articol] - Tanas, Ghenadie (CEP USM, 2020)
Most often, states with a consolidated and stable democracy have systems of law that effectively protect the institutions of the rule of law and the democratic exchange of state power within an honest electoral competition. Due to the legal maturity of the legal systems, the criminal laws in Germany, Austria and the United Kingdom, the study of the issues related to the regulation and incrimination of the corruption facts of the voters and other election crimes, in the legislation of the listed states, is of particular interest. The aspects of incrimination are analyzed, mechanisms for voter accountability and mechanisms to prevent and combat fake news.
LEGAL-CRIMINAL ANALYSIS OF LEGISLATION IN SOME STATES WITH A CONSOLIDATED DEMOCRACY ON THE INCIMINATION OF ELECTION OFFENSESAND THE ELECTION CORRUPTIONS
Keywords: criminal law; election crimes; corruption of voters; infracțiuni electorale